2017
DOI: 10.3847/2041-8213/aa9476
|View full text |Cite
|
Sign up to set email alerts
|

Block-induced Complex Structures Building the Flare-productive Solar Active Region 12673

Abstract: Solar active region (AR) 12673 produced 4 X-class, 27 M-class, and numerous lower class flares during its passage across the visible solar disk in September 2017. Our study is to answer the questions why this AR was so flare-productive and how the X9.3 flare, the largest one of the last decade, took place. We find that there was a sunspot in the initial several days, and then two bipolar regions emerged nearby it successively. Due to the standing of the pre-existing sunspot, the movement of the bipoles was blo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
97
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(102 citation statements)
references
References 46 publications
2
97
1
2
Order By: Relevance
“…The unique non-potential characteristics found in this study are in agreement with previous studies and interpretations. Studies of this AR 12673 by Yang et al (2017) showed that the flux rope eruption is triggered by kinkinstability because of the exceeding critical twist. They had proposed a block-induced complex structure for a flare-productive AR.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The unique non-potential characteristics found in this study are in agreement with previous studies and interpretations. Studies of this AR 12673 by Yang et al (2017) showed that the flux rope eruption is triggered by kinkinstability because of the exceeding critical twist. They had proposed a block-induced complex structure for a flare-productive AR.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…AR 12673 starts emerging from September 2 at disk position E11S08 into pre-existing positive sunspot polarity (SP). As described by Yang et al (2017, Figure 1), the emergence on September 3 is through two bipolar regions (Hou et al 2018). The proper and shear motion of these emerging patches was interacted by the pre-existing spot and formed a large sheared main PIL.…”
Section: Observations and Overviewmentioning
confidence: 98%
“…Hence it keeps almost stable. The two notable plumes mainly result from two big ARs, i.e., AR12674 and AR12673 (Yang et al 2017;Yan et al 2018). They occurred on the solar disc with large tilts around 2017 September 5th located at northern and southern hemispheres, respectively.…”
Section: Updated Predictability Of Cycle 25mentioning
confidence: 99%
“…Solar NOAA active region (AR) 12673, which was observed in September 2017, was remarkable for its complex structure and extraordinary flare productivity-the highest in Solar Cycle 24 (Yang et al 2017;Attie et al 2018;Hou et al 2018). It produced 4 flares above X1 class and 8 flares above M3 class; moreover, its X-9.3 flare (on 2017 September 6, 11:53 UT) was the most intense one since 2005 (see, e.g., Sun & Norton 2017).…”
Section: Introductionmentioning
confidence: 99%